Síntese e aplicação de uma azida de celulose na imobilização de enzima lipase Candida antarctica CALB por reação do tipo “click” CuAAC - Ferreira, Marcos Vinícius (2023)
Enzymatic catalysts play a fundamental role in the development of various industrial processes, having generated promising results, particularly in the field of renewable energy. However, one of the problems associated with the use of free enzymes is keeping their stability in the reaction medium and the difficulty of recovering them, therefore, limiting their reuse and increasing process costs. In this context, a support/enzyme bioconjugate was developed in this work through the chemical binding, using a click reaction of alkyne/azide cycloaddition catalyzed by copper (CuAAC), of the lipase enzyme to a modified cellulose support. In the context of cellulose, which does not naturally possess groups compatible with this click reaction, the synthesis of cellulose tosylate (MCC-Tos) was adopted, followed by its subsequent transformation into azide cellulose (MCC-Az). For this purpose, the reaction variables such as time, temperature, and molar ratio of p-toluenesulfonyl chloride to anhydroglucose unit (Tos:UAG) for the synthesis of MCC-Tos in a heterogeneous phase were optimized using experimental design by Doehlert matrix. From this design, it was observed that the most significant variables were the molar ratio (RM) and the reaction time. Thus, the MCC-Tos derivative was produced under extrapolated optimized conditions (MCC-Otm), namely at 30 °C, 144 h, and MR 10:1 (Tos:AGU), with a degree of substitution (GS) of 1.72. MCC-Tos Otm was used as a precursor in the synthesis of MCC-Az Otm. Structural analyses using infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), solid-state 13C nuclear magnetic resonance (RMN 13C-CP/MAS), X-ray diffractograms (DRX), and surface area and porosity analysis (ASAP) confirmed the obtainment of these derivatives, showing a reduction in crystallinity (by approximately 20%) and an increase in the surface area of MCC-Az (from 0.924 to 52.995 m2 g-1, compared to MCC). Regarding the insertion of the propargyl group into the Candida antarctica B lipase (CalB), forming the CalB-Prop, spectroscopic techniques such as FTIR, UV-vis, and fluorescence revealed a conformational change in the enzyme after modification, but without extending to changes in its active form. In the immobilization of CalB-Prop on the MCC-Az support, spectroscopic techniques indicated binding through CuAAC reaction, with a new conformational change in the enzyme that also reflected changes in its active form. The incorporation efficiency (%EI) of CalB was estimated at 24.63%, indicating a covalent immobilization confirmed by a reduction in the intensity of the azide band by 19.54%. Despite this low %EI, the MCC-CalB bioconjugate showed a specific enzymatic activity (AEE) in the reaction with p-nitrophenyl palmitate equal to 84.87 LU g-1. The results suggest the efficiency of the proposed cellulose derivatives and bioconjugate synthesis, paving the way for kinetic evaluations, enzymatic activity, and reuse in transesterification reactions with vegetable oils.